Improvement of crossflow aerodynamic predictions for forwarded flight at all advance ratios - Hodara, J.; Smith, M.J. (My University, 2014)
The aerodynamics of rotorcraft in forward flight, particularly at high advance ratios, are highly complex. Of particular interest is the impact of crossflow on forward flight performance that occurs over large portions of the rotor disk. Results from high fidelity numerical experiments on an infinite yawed wing, previously validated with experimental data for a wide range of Mach numbers, angles of attack and yaw angles, are analyzed for use in airfoil tables (C81 tables) for rotorcraft comprehensive codes. Investigation of the errors introduced by interpolation of airfoil tables and application of the Betz crossflow and independence principles in various flight regimes has been completed, including further understanding of the physics driving the behavior of the integrated airfoil performance. The analysis has also been extended to reverse flow conditions, which become significant at high advance ratios. Empirical corrections have been developed that improve the lift, drag and pitching moment predictions of the crossflow model.